Millennial Consumer Preferences for Healthy Instant Noodle Products in East Java (Choice Experiment Method) - Prameswari, Syera Aqila; Toiba, Hery; Andriani, Dwi Retno; Noor, Arif Yustian Maulana (HABITAT, 2025)
Healthy living is now a popular lifestyle among the millennial generation, health consciousness is a concern for some who prefer to engage in activities that can be beneficial to the body, one of which is paying attention to dietary intake. Porang (Konjac) is an alternative raw material for processed products, especially konjac noodles, and those containing gluten. At present, there is little consumer research, apart from the fact that it is a relatively new product on the market, previous studies have focused on the glucomannan content of konjac noodle products. The results of the multinomial logit analysis for the five attributes, calorie content, fibre content, food additives and price, show that respondents prefer products with low calorie content, high fibre content, using natural food additives and the lowest price category. The attribute that consumers consider important, the use of natural food additives and fiber content, comes last. The implications of this study could be considered by manufacturers who want to produce konjac noodle to add natural food additives and list them on the label on the packaging. Building economical packaging and partnerships to achieve lower prices and attract consumers.